2015
DOI: 10.1177/1753944715587424
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiac L-type Ca2+ current by angiotensin-(1-7): normal versus heart failure

Abstract: Objective Recent evidence has shown that, in heart failure (HF), clinically relevant concentrations of angiotensin-(1-7) [Ang-(1-7)] counteracts angiotensin II induced cardiac depression and produces positive inotropic effects in both left ventricle (LV) and myocytes. However, the underlying electrophysiological mechanism is unclear. We investigated the role and mechanism of Ang-(1-7) on LV myocyte L-type calcium current (ICa,L) responses in normal state and in HF. Method We compared the effect of Ang-(1-7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
(81 reference statements)
2
17
0
Order By: Relevance
“…All had clear evidence of HF (anorexia, edema, and pulmonary congestion). In line with our previous work and that of others,(23;25;27) the total infarction area in ISO-injected rats averaged about 36 ± 5%. Diffuse subendocardial necrosis and pronounced LV enlargement with increased LV volume were also observed.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…All had clear evidence of HF (anorexia, edema, and pulmonary congestion). In line with our previous work and that of others,(23;25;27) the total infarction area in ISO-injected rats averaged about 36 ± 5%. Diffuse subendocardial necrosis and pronounced LV enlargement with increased LV volume were also observed.…”
Section: Resultssupporting
confidence: 93%
“…(2427) Pathologic cardiac changes in ISO-treated rats resemble those of myocardial infarction (including LV structural remodeling, myocardial necrosis, eccentric hypertrophy with reduced contractile functional performance, and decreased β-adrenergic reserve). (2326;28)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is confirmed by a study of Mercure et al, who showed that a chronic overproduction of cardiac Ang(1-7) in mice did not affect heart function under normal hemodynamic conditions (Mercure et al, 2008). Regarding heart function, it is known that Ang(1-7) can mitigate isoprenaline effects (Martins Lima et al, 2013), but has no effect on intracellular calcium handling (Dias-Peixoto et al, 2008;Zhou et al, 2015) in normal cardiomyocytes.…”
Section: Discussionsupporting
confidence: 73%
“…It has been proposed that these intracrine effects of Ang II might be of particular importance during pathological conditions such as MI, when heart excitability is already enhanced [De Mello, 2013]. Ang II has also been shown to increase the percentage and velocity of myocyte shortening, increase the velocity of myocyte relengthening and increase peak systolic transient calcium levels [Zhou et al 2015]. …”
Section: Effects Of Ang IImentioning
confidence: 99%